2009
DOI: 10.1016/j.jcin.2009.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation in 3 Months Duration of Neointimal Coverage After Zotarolimus-Eluting Stent Implantation by Optical Coherence Tomography

Abstract: Most of the stent struts were covered with neointima, and late acquired malapposition was not found at 3 months after ZES implantation. Therefore, the current study demonstrated that ZES might have a favorable in vivo vascular response at 3 months after stent implantation. (Evaluation of Zotarolimus Eluting Stent at 3 Months Using Optical Coherence Tomography [ENDEAVOR OCT]; NCT00815139).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 27 publications
2
59
1
2
Order By: Relevance
“…This has also been demonstrated in direct comparison against the Taxus TM -and the Cypher TM -Stent [12,13]. Recently, it has been proven, that the Endeavor TM -Stent showed better endothelial strut coverage even in myocardial infarction in comparison to other DES [32][33][34]. However, the SORT OUT III trial revealed a low (1%) but significantly higher rate of definite stent-thrombosis after nine months in comparison to sirolimus-eluting stents [23].…”
Section: Follow-upmentioning
confidence: 92%
“…This has also been demonstrated in direct comparison against the Taxus TM -and the Cypher TM -Stent [12,13]. Recently, it has been proven, that the Endeavor TM -Stent showed better endothelial strut coverage even in myocardial infarction in comparison to other DES [32][33][34]. However, the SORT OUT III trial revealed a low (1%) but significantly higher rate of definite stent-thrombosis after nine months in comparison to sirolimus-eluting stents [23].…”
Section: Follow-upmentioning
confidence: 92%
“…14 Several clinical studies have also supported the safety of ZES. In optical coherence tomography studies, most of the stent struts were covered with neointima at 3 months after ZES implantation, 15 and exposure of stent struts and thrombi was observed less frequently in patients undergoing PCI with ZES than in those undergoing PCI with SES at 9 months follow up. 16 In other OCT studies, uncovered struts were frequently observed in SES at 9-12 months.…”
Section: Favorable Outcomes With a Short Duration Of Dual Antiplatelementioning
confidence: 95%
“…12 Several animal and human studies support the safety of ZES. [13][14][15][16][17] Theoretically, the duration of dual antiplatelet therapy can be shorter with ZES than with other stents. This study aims to determine the feasibility of 3-month dual antiplatelet therapy after ZES implantation in relatively lowrisk patients with coronary artery disease.…”
Section: -Month Clopidogrel For Zotarolimus-eluting Stentsmentioning
confidence: 99%
“…3 Clinical investigation has shown that the E-ZES had nearly complete neointimal coverage at 3 months. 4 Sufficient arterial repair characterized by less development of thrombus, and substantial neointima formation occurred by 4 months after E-ZES implantation. 5 Such more rapid arterial repair than with other DES may contribute to neointimal stability.…”
Section: Article P 650mentioning
confidence: 99%